Differences in Fluoride Content of Drinking Water in Mountain and Coastal Communities - Ni Wayan Mariati; Marcellino Jonathan Lie; Dinar Arum Wicaksono (Green Publisher Indonesia, 2026)
Dental and oral health are essential components of overall health. One of the common dental issues is dental fluorosis, which results from excessive fluoride exposure during tooth development. Such exposure often originates from drinking water, particularly in areas with naturally high fluoride concentrations. Fluoride occurs in both surface and well water, but surface water typically contains lower fluoride levels. In contrast, the fluoride concentration in well water depends on several factors, including the geological, chemical, and physical characteristics of the aquifer, soil and rock porosity, acidity, temperature, chemical interactions among elements, and well depth. Previous studies have reported variations in fluoride levels between mountainous and coastal regions. This study aimed to determine differences in fluoride content in drinking water between mountainous and coastal communities. A comparative study design was used, with well water from Lahendong Village, South Tomohon District (mountainous area), and Meras Village, Bunaken District, Manado City (coastal area) as the population. The sample consisted of five water samples from each region, selected through purposive sampling. Fluoride levels were analyzed using a spectrophotometer. Results showed that the mean fluoride concentration in drinking water from mountainous areas was 0.108 mg/L, while in coastal areas it was 0.298 mg/L. Statistical analysis using an unpaired t-test indicated a significant difference (p < 0.05). The study concludes that fluoride content in drinking water from mountainous regions is significantly lower than that found in coastal areas, suggesting that geographical and geological conditions influence natural fluoride concentrations in groundwater.